Pengaruh Perputaran Kas, Kecukupan Modal Dan Pertumbuhan Kredit Terhadap Profitabilitas Lembaga Perkreditan Desa (LPD) - Ida Bagus Gede Pradnyana; Ni Putu Ayu Kusumawati; Ni Wayan Alit Erlinawati (Hita Akuntansi dan Keuangan, 2023)
The amount of profit received by an LPD is very dependent on the ability of the management to manage various assets and debts owned. This research will focus on the factors that affect the level of profitability of LPDs such as cash balances, capital adequacy, and credit growth. In this study, LPDs in Payangan District were chosen to be the research location with a population of 48 LPDs in Payangan District. The sample of this study consisted of 96 financial statements from 32 LPDs that were declared active during the 2018-2020 period. This study uses multiple linear regression analysis techniques with results showing that the profitability of LPDs in Payangan District can be increased if the LPD cash turnover is getting better, capital adequacy is stable, and credit turnover is good.